2013
DOI: 10.1093/nar/gkt828
|View full text |Cite
|
Sign up to set email alerts
|

On the structural basis and design guidelines for type II topoisomerase-targeting anticancer drugs

Abstract: Type II topoisomerases (Top2s) alter DNA topology via the formation of an enzyme–DNA adduct termed cleavage complex, which harbors a transient double-strand break in one DNA to allow the passage of another. Agents targeting human Top2s are clinically active anticancer drugs whose trapping of Top2-mediated DNA breakage effectively induces genome fragmentation and cell death. To understand the structural basis of this drug action, we previously determined the structure of human Top2 β-isoform forming a cleavage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
146
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(155 citation statements)
references
References 37 publications
(54 reference statements)
7
146
0
2
Order By: Relevance
“…5,26,27 In the case of Top2β, each monomer of the Top2 dimer accommodates one inhibitor molecules of the Top2-DNA cleavage complex (Top2cc) (Figure 3). 5 Similar mode of binding is observed in the case of the topoisomerase IV complex with the formation of a binding pocket at the protein-DNA interface when the binary system is subjected to treatment with a drug.…”
Section: Top2 Inhibitorsmentioning
confidence: 99%
“…5,26,27 In the case of Top2β, each monomer of the Top2 dimer accommodates one inhibitor molecules of the Top2-DNA cleavage complex (Top2cc) (Figure 3). 5 Similar mode of binding is observed in the case of the topoisomerase IV complex with the formation of a binding pocket at the protein-DNA interface when the binary system is subjected to treatment with a drug.…”
Section: Top2 Inhibitorsmentioning
confidence: 99%
“…The glycosidic moiety may even be replaced with a variety of other moieties such as the polyamines found in F14512 40 and in TOP-53 or a p -nitrophenyl moiety found in GL-311. 16 It has been shown in the PDB ID: 3QX3 X-ray structure of two molecules of etoposide complexed to cleaved DNA and topoisomerase IIβ 8,9 that the glycosidic moiety of etoposide occupies a spacious binding pocket in the protein with few protein interactions. This result explains why etoposide analogs are relatively insensitive to substituents that replace or substitute on the glycosidic moiety.…”
Section: Resultsmentioning
confidence: 99%
“…8,9 In this structure the glycosidic moiety of etoposide occupies a spacious binding pocket in the protein. The bound epipodophyllotoxin moiety of etoposide, unlike planar DNA intercalators that stack with two bases, stacks only with a single +5 guanine base in a DNA deformed structure.…”
Section: Introduction1mentioning
confidence: 99%
See 1 more Smart Citation
“…Wu et al (2013) determined the highresolution crystal structures of Top2β cleavage complexes stabilized by MTX. Huang and Lin (2014) demonstrated that this drug formed a weak cleavage complex with Top2β as compared with that formed with Top2α.…”
Section: Topoisomerase Inhibitionmentioning
confidence: 99%